Multiple Ligament Reconstructions of the Knee and Posterolateral Corner - Floyd, Edward R. (Arthrosc Tech, 2021)
Injuries to the knee involving multiple ligaments occur in a variety of circumstances and require careful assessment and planning. A wide constellation of injuries can occur with causes sufficiently traumatic to produce bicruciate ligament deficiency, and this technical report will describe diagnosis, treatment and rehabilitation for a knee dislocation with lateral injury (KD-III-L on the Schenk classification). Reconstruction in the acute setting is preferred, with anatomic-based, single-bundle anterior cruciate ligament reconstruction, double-bundle posterior cruciate ligament reconstruction, and anatomic reconstruction of the posterolateral corner using two grafts for the 3 primary posterolateral corner stabilizers. Tunnel orientation to prevent convergence and sequence of graft tensioning and fixation are discussed as well. Successful outcomes have been achieved using these anatomic-based reconstruction techniques along with appropriate rehabilitation and bracing.